Nomadic theatre : mobilizing theory and practice on the European stage - Nibbelink, Liesbeth Groot (Thinking through theatre, 2019)
Fluid stages, morphing theater spaces, ambulant spectators, and occasionally disappearing performers: these are some of the key ingredients of nomadic theater. They are also theater's response to life in the 21st century, which is increasingly marked by the mobility of people, information, technologies, and services. While examining how contemporary theater exposes and queries this mobile turn in society, the author introduces the concepts of nomadic theater as a vital tool for analyzing how movement and mobility affect and implicate the theater, how this makes way for local operations and lived spaces, and how physical movements are stepping stones for theorizing mobility at large. This book focuses on ambulatory performances and performative installations, asking how they stage movement and in turn mobilize the stage. By analyzing the work of leading European artists including Rimini Protokoll, Dries Verhoeven, Ontroerend Goed, and Signa, this book demonstrates that mobile performances radically rethink the conditions of the stage and alter our understanding of spectatorship. This book instigates connections across disciplinary fields and feeds dramaturgical analysis with insights derived from media theory, urban philosophy, cartography, architecture, and game studies. It illustrates how theater, as a material form of thought, creatively and critically engages with mobile existence both on the stage and in society.